Elastic anisotropies, electronic structures and tensile properties of anti-perovskite M3AlC (M=Ti, Co, Fe, Mn) phases: A first-principles calculation. (August 2022) - Wang, Renfu; Yang, Ancang; Bao, Longke; Peng, Mingjun; Duan, Yonghua
Abstract: Anti-perovskite material is a new functional material with excellent hydrogen storage and energy storage, which has great potential for reverse expansion. In this paper, the structural stability, mechanical properties, thermodynamic properties, electronic structure and tensile properties of M3 AlC compounds were studied by using the first-principle calculation based on density functional theory. The results showed that the elastic modulus, sound velocity and minimum thermal conductivity of M3 AlC are anisotropic, and the density of States and charge difference density showed that M3 AlC compounds contain not only strong covalent bonds, but also metal bonds and ionic bonds. Mulliken population analyzed the overall bonding strength. Finally, the tensile strength of M3 AlC compounds was also discussed. Which provide a theoretical framework for the further study of anti-perovskite material M3 AlC compounds. Highlights: Formation enthalpy and phonon spectrum show that M3 AlC compounds are stable. M3 AlC compounds are anisotropic in elastic modulus. Sound velocities and minimum thermal conductivities of M3 AlC compounds are also anisotropic. The order of tensile strength values of M3 AlC compounds is Fe3 AlC > Mn3 AlC > Co3 AlC > Ti3 AlC.